2012
DOI: 10.1111/fwb.12009
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐ and interspecific differences in nutrient recycling by European freshwater fish

Abstract: Summary 1. We measured N and P excretion rates of 470 individuals belonging to 18 freshwater fish species widespread in Western Europe. We assessed the effect of body mass on excretion rates at both the intra‐ and interspecific levels. 2. The high variability in per capita N and P excretion rates was mainly determined by differences in body mass. The scaling coefficients of allometric relationships for both N and P excretion rates were significantly lower than 1 (mean ± SE, 0.95 ± 0.04 and 0.81 ± 0.05, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 46 publications
(134 reference statements)
2
20
0
1
Order By: Relevance
“…We logged terms (base 10) and used ordinary least squares (OLS) regression (SPSS, version 12.0.1) to create a predictive allometric cutthroat trout and lake trout excretion model based on individual dry mass. The slope of our cutthroat trout and lake trout model (0.70 using reduced major axis linear regression for comparison only) was similar to other slopes measured for Bonneville cutthroat trout (0.71; Oncorhynchus clarkii utah), kokanee salmon (0.96; Oncorhynchus nerka; Wheeler et al 2014), rainbow trout (0.62; Oncorhynchus mykiss), brook trout (0.47; Salvelinus fontinalis; Paulson 1980, Sereda et al 2008, and brown trout (0.75; Salmo trutta; Villéger et al 2012). Reduced major axis linear regression allows biologically interpreting the slope parameter in a symmetric relationship (Warton et al 2006) whereas our predictive allometric OLS model allowed us to estimate the excretion rate based on the trout mass.…”
Section: Excretion Fluxes In Yellowstone Lake and Clear Creeksupporting
confidence: 79%
“…We logged terms (base 10) and used ordinary least squares (OLS) regression (SPSS, version 12.0.1) to create a predictive allometric cutthroat trout and lake trout excretion model based on individual dry mass. The slope of our cutthroat trout and lake trout model (0.70 using reduced major axis linear regression for comparison only) was similar to other slopes measured for Bonneville cutthroat trout (0.71; Oncorhynchus clarkii utah), kokanee salmon (0.96; Oncorhynchus nerka; Wheeler et al 2014), rainbow trout (0.62; Oncorhynchus mykiss), brook trout (0.47; Salvelinus fontinalis; Paulson 1980, Sereda et al 2008, and brown trout (0.75; Salmo trutta; Villéger et al 2012). Reduced major axis linear regression allows biologically interpreting the slope parameter in a symmetric relationship (Warton et al 2006) whereas our predictive allometric OLS model allowed us to estimate the excretion rate based on the trout mass.…”
Section: Excretion Fluxes In Yellowstone Lake and Clear Creeksupporting
confidence: 79%
“…Another potential factor that may confound dietary effects on excretion is that excretion rates of N and P scale differently with body mass (Torres & Vanni, ). If consumers grow at different rates when feeding on diets of differing elemental composition, differences in body mass alone could account for differences in excretion ratios (Villéger et al ., ,b). We were unable to correct for the different allometries of N and P excretion because the units in which excretion was reported varied between studies, but all studies reported excretion as some function of fish mass.…”
Section: Discussionmentioning
confidence: 97%
“…from 12 to 350 μS cm −1 ; Villéger et al . ). A 3‐m copper cathode and a 20‐cm‐diameter ring anode were used, because a large amount of the fish fauna is small sized (mean fish body size: 49 ± 55 mm, range 10–390 mm), making large anodes inefficient for the capture of a substantial part of the fish.…”
Section: Methodsmentioning
confidence: 97%